Floating tones in Ga - Mary Paster (Studies in African Linguistics, 2003)
This paper provides robust empirical evidence for floating tones in Ga, a Kwa language of Ghana. As will be shown, floating tones are crucial to an analysis of verbal tense/aspect/mood distinctions. I begin by describing two tonal processes, the HL rule and Plateauing. While these are regular processes of the language, both are blocked in the perfective. I show that the blockage is the result of a floating low tone that marks the perfective, and that the floating tone marker explains other anomalous tonal effects in the perfective. I then give an analysis of floating tone prefixes that mark certain tenses/aspects/moods by associating to the subject prefix, thus overwriting the lexical tone of the subject prefix. Finally, I give examples of suffixed floating that mark tense/aspect/mood by associating to verb stems, causing the underlying stem tones to delink. In these tenses/aspects/moods, we find evidence for an underlying L vs. toneless contrast, constituting another phenomenon where, as with floating tones, there is a mismatch between the number of tones and tonebearing units. Thus, a major prediction of Autosegmental Phonology (Goldsmith 1976, Clements and Ford 1979) is borne out in Ga.